Faktor-Faktor Yang Berhubungan Dengan Tingkat Literasi Kesehatan Pasien Pelayanan Kedokteran Keluarga - Santosa, Karina Samaria; Pratomo, Hadi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
ABSTRACT Introduction: Health literacy is crucial for health management, but still has become a problem in many countries. The objective of this study was to assess patient’s health literacy levels in Kiara Family Medicine Clinic of the Medical Faculty University of Indonesia and its determinants. Method: This was quantitative research with cross- sectional design. The population was all patients visiting the clinic during the data collection period. The samples were patients who met the inclusion and exclusion criteria, chosen with consecutive sampling technique. Minimal sample size was counted using different proportion hypothesis test formula, results in minimum of 134 respondents. The independent variables were age, language, ethnicity, sex, level of education, length of education, occupation, income, access to health services, and health information access. The dependent variable was levels of health literacy.The instruments were questionnaires on health literacy determinats and Newest Vital Sign adapted in bahasa Indonesia (NVS-I). Univariate, bivariate (chi-square test), and multivariate (logistic regression) analyses were conducted. Results: 27.4% of respondents had high health literacy level and 72.6% of respondents had low health literacy level. Factors associated with health literacy levels were health information access and length of education. The most dominant influencing factor of health literacy was accessibility to health information. Conclusion: Most of the patients had low health literacy level with NVS-I measurement. The factor most associated with health literacy level was health information access. More efforts are needed in promoting patient’s health literacy through improving health information access. Keywords: family medicine, health information access, health literacy